2011
DOI: 10.1017/s002211201000618x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear waves in counter-current gas–liquid film flow

Abstract: We investigate the dynamics of a thin laminar liquid film flowing under gravity down the lower wall of an inclined channel when turbulent gas flows above the film. The solution of the full system of equations describing the gas-liquid flow faces serious technical difficulties. However, a number of assumptions allow isolating the gas problem and solving it independently by treating the interface as a solid wall. This permits finding the perturbations to pressure and tangential stresses at the interface imposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 56 publications
5
84
0
2
Order By: Relevance
“…As the gas flow rate is further increased, the system again becomes convectively unstable with the localised disturbances propagating upwards. We find that the upper limit of the absolute instability region is close to the 'flooding' point associated with the appearance of large-amplitude standing waves, as obtained in Tseluiko & Kalliadasis (2011), and our analysis can therefore be used to predict the onset of flooding. We also find that an increase in the angle of inclination of the channel requires an increased gas flow rate for the onset of absolute instability.…”
Section: Journal Of Fluidsupporting
confidence: 71%
See 4 more Smart Citations
“…As the gas flow rate is further increased, the system again becomes convectively unstable with the localised disturbances propagating upwards. We find that the upper limit of the absolute instability region is close to the 'flooding' point associated with the appearance of large-amplitude standing waves, as obtained in Tseluiko & Kalliadasis (2011), and our analysis can therefore be used to predict the onset of flooding. We also find that an increase in the angle of inclination of the channel requires an increased gas flow rate for the onset of absolute instability.…”
Section: Journal Of Fluidsupporting
confidence: 71%
“…AlthoughÓ Náraigh et al (2011Náraigh et al ( , 2013 found that the waviness induced Reynolds stresses do not play a significant role in the stability of the interface for the parameter values they considered, it should be noted that the simple quasi-laminar assumption does not provide good agreement with experiments -e.g. by Thorsness et al (1978) -as shown in Tseluiko & Kalliadasis (2011). Also, the conclusion ofÓ Náraigh et al (2011Náraigh et al ( , 2013 on the impact of waviness induced Reynolds stresses on the interfacial instability seems to be in contradiction with the results presented in Tseluiko & Kalliadasis (2011).…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations